1999
DOI: 10.1161/01.hyp.33.1.248
|View full text |Cite
|
Sign up to set email alerts
|

Telemetry for Cardiovascular Monitoring in a Pharmacological Study

Abstract: Abstract-Radio-telemetry systems offer the ability to measure blood pressure and heart rate in experimental models of hypertension without the stress artifacts induced by some other methods. We therefore aimed to develop improved, nonparametric regression methods for radio-telemetry data and to use these to assess the effects of pharmacological interventions on cardiac and vascular hypertrophy in the stroke-prone spontaneously hypertensive rat. One control group and 5 groups treated either with losartan (alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 34 publications
1
42
0
1
Order By: Relevance
“…Stress imposed on rats in the tail-cuff BP measurement might be a major cause of the discrepancy between the BP data measured by the tail-cuff method and by the telemetry. 13,14 In any case, these observations indicate the difficulty in analyzing QTLs for BP.…”
Section: Discussionmentioning
confidence: 99%
“…Stress imposed on rats in the tail-cuff BP measurement might be a major cause of the discrepancy between the BP data measured by the tail-cuff method and by the telemetry. 13,14 In any case, these observations indicate the difficulty in analyzing QTLs for BP.…”
Section: Discussionmentioning
confidence: 99%
“…Other analytic methods for examining BP fluctuations in both the frequency and the time domain have also been developed and used. 37,57 The high-fidelity BP phenotyping that is achievable with BP radiotelemetry and with direct measurements through external catheter systems has also provided an invaluable tool for the investigation of genetic determinants of BP regulation. Identifying quantitative trait loci for BP using genetic strategies has been of intense interest in recent years.…”
Section: Advantages and Applicationsmentioning
confidence: 99%
“…Indeed, other investigators using continuous radiotelemetry measurements in SHRsp have found that the superior ability of losartan or perindopril to attenuate cardiac and vascular hypertrophy, in comparison with a hydralazine/ hydrochlorothiazide combination, may also be related to their superior ability to reduce blood pressure. 7 Thus, the findings of Griffin et al may be relevant to the protective effects of RAAS blockade on a variety of forms of target organ damage. These kinds of radiotelemetry studies not only raise questions about claims regarding BP-independent mechanisms that mediate the protective effects of RAAS blockade, but they also remind us of what should be obvious but is so often ignored in hypertension research: that to draw valid conclusions about the relationship between blood pressure and any other variable, it is important to obtain a thorough and accurate assessment of all phenotypes-including blood pressure!…”
mentioning
confidence: 99%